Sentencing as a Human Process - Hogarth, John (Canadian studies in criminology, 1971)
Sentencing is not a neutral or mechanical act; it is a human process, highly charged affectively and motivationally. Sentencing decisions take place in a social environment of laws, facts, ideas, and people. This study of sentencing behaviour is primarily concerned with the mental processes involved in decision-making. It is based on intensive interviews and on measures of the information-processing ability of seventy-one full-time judges in Ontario. The work covers such topics as: problems of sentencing (particularly existing disparities); social and economic background of judges and their varying penal philosophies; the nature and measurement of judicial attitudes toward crime; punishment and related issues; prediction of sentencing behaviour based on attitude scales (which the author has constructed) and also on 'fact patterns perceived by judges'; and the impact of social and legal constraints on the sentencing process. The study concludes that there exists a very high correlation between a judges definition of situation and the sentence which he imposes and that while sentences meted out for a particular law violation under similar circumstances may differ among judges, judges are 'highly consistent within themselves.' Using these conclusions the author constructs a model of judicial behaviour and shows how this model can be used to predict and to explain sentencing and breaks new ground in the use of the social and behavioural sciences as sources of data to explain the sentencing process